Health care professional attitude and motivation during covid-19: A case of health sector of oman - AlAbri I.; Bte Siron R. (EManuscript Technologies, 2023)
Motivations, whether intrinsic or extrinsic, provide stimulus to work in normal and challenging situations. This study focuses on the motivational level, attitude and professional practices among health professional workers in Oman. Data was collected from health professionals using selfadministrative interviews and questionnaire using cross-sectional data collection method and convenient sampling technique. The findings indicate that the moral of the health professional workers was low in the beginning but was gradually built receiving motivational and psychological support from general public and officials. The study also recommends developing inclusive health protocols and general public awareness campaign need to be launched to comprehend future pandemics in better way. 2020 EManuscript Technologies. All rights reserved.